مدى توافر متطلبات استخدام التعليم الالكتروني في تدريس مادة الرياضيات بالمرحلة الثانوية من وجهة نظر المعلمين - آمنة بشير هاشم عبد الله (White Nile Journal for Studies and Research, 2014)
This research aims at recognizing the range of the availability of the requirements of E-learning usage for teaching mathematics at secondary schools from the viewpoint of teachers in White Nile State. Dewaim locality. The researcher used the analytic descriptive method and designed questionnaire as research tools the research society formed from 115 teachers (female and male) and from them she had 115 teachers as the research - sample.After applying research procedure on the research - sample the researcher analyzed the data and deduced the arithmetic>s means, the standard deviations. The most important findings of the research are the following 1. The requirements of E-learning usage for teaching mathematics at secondary schools regarding curriculum are available.2. The requirements of E-learningnusage for teaching mathematics at secondary schools regarding teachers are not strong 3. The requirementsnofnnE-learningnusage for teaching mathematics at secondary schools regarding learners are few 4. The nnrequirements of E-learning usage for teaching mathematics at secondary schools regarding educational environment are few